MEDAN MAKNA AKTIVITAS MENGANYAM MASYARAKAT MELAYU SAMBAS - Regina Sumarna; Amriani Amir; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research deals with linguistics and is focused on the semantic field, namely the field of meaning. This study aimed to describe the components of meaning and the types of meanings contained in the field of meaning of the weaving activities of the Malay people of Sambas. The method used in this research was descriptive method. The form of research used is qualitative research. The data used in this study was the source of data in this research is the Sambas Malay language which is spoken by informants to provide information about weaving activities. Data collection techniques in this study were fishing techniques, proficiency at hand, note, record. Data collection tool in this study is the researcher as a key instrument. In addition, researchers also used list of questions, note sheets, recording tools. Based on the results of field analysis, the meaning of weaving activities was divided into 2 parts, namely weaving activities using tools and weaving activities not using tools. Components of the meaning of the lexeme of weaving activity in the Malay language Sambas were divided based on the semantic characteristics of the actor, body position, tools, time, results, goals, and texture. It was found that in the Sambas Malay language there are 10 leksem in the field of meaning of weaving activity and 2 in the collocative field.Keywords: field of meaning, weaving activity, semantics